2011
DOI: 10.1124/dmd.110.037671
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Amiodarone Metabolites in Human Bile by Ultraperformance Liquid Chromatography/Quadrupole Time-of-Flight Mass Spectrometry

Abstract: ABSTRACT:Amiodarone is recognized as an effective drug in the treatment of arrhythmias. Previous experiments demonstrated that mono-Ndesethylamiodarone (MDEA) was the major circulating metabolite in humans. In addition, dealkylation, hydroxylation, and deamination were minor metabolic pathways. The purpose of this study was to identify the metabolites of amiodarone in the bile obtained from patients with T-tube drainage after oral drug administration. Amiodarone metabolism in vitro was also investigated using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 22 publications
(27 reference statements)
2
44
0
Order By: Relevance
“…In this study, NMR analysis revealed that the hydroxylated metabolite is a mixture of two distinct products, 4-and 3-hydroxyamiodarone. These two metabolites have been recently identified in biliary excreta in human subjects after amiodarone dosing (Deng et al, 2011). Deng et al (2011) identified 33 metabolites derived from amiodarone excreted in human bile by mass spectral fragmentation patterns or confirmation by comparison of chromatographic retention times and mass spectra with available reference standards.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, NMR analysis revealed that the hydroxylated metabolite is a mixture of two distinct products, 4-and 3-hydroxyamiodarone. These two metabolites have been recently identified in biliary excreta in human subjects after amiodarone dosing (Deng et al, 2011). Deng et al (2011) identified 33 metabolites derived from amiodarone excreted in human bile by mass spectral fragmentation patterns or confirmation by comparison of chromatographic retention times and mass spectra with available reference standards.…”
Section: Discussionmentioning
confidence: 99%
“…These two metabolites have been recently identified in biliary excreta in human subjects after amiodarone dosing (Deng et al, 2011). Deng et al (2011) identified 33 metabolites derived from amiodarone excreted in human bile by mass spectral fragmentation patterns or confirmation by comparison of chromatographic retention times and mass spectra with available reference standards. Our work confirms the formation of the 4-and 3-hydroxyamiodarone by CYP2J2 in HLM, and it is likely that the former metabolite can be made in extrahepatic tissues that may contribute to the overall in vivo formation.…”
Section: Discussionmentioning
confidence: 99%
“…3C). We propose M9 as 4Ј-OH-THJ-018 because -hydroxylation and -1-hydroxylation were usually the primary biotransformations for drugs with aliphatic side chains and displayed similar physicochemical properties (22)(23)(24). This phenomenon also was observed for 5Ј-OH-JWH-018 and 4Ј-OH-JWH-018 (11 ).…”
Section: '-Hydroxylation and Further Oxidation And Glucuronidationmentioning
confidence: 99%
“…Frozen microbial stock culture of C. blakesleana ATCC9244 was first incubated in 250-ml flasks containing potato dextrose agar at 28°C for 7 days in a rotary shaker set to 220 rpm (Asha and Vidyavathi, 2009;Deng et al, 2011). The seed culture (5.0 ml) was then inoculated into 250-ml flasks containing 50 ml of biotransformation medium consisting of dextrose (1.0 g), yeast extract (0.25 g), peptone (0.25 g), NaCl (0.25 g), and K 2 HPO 4 (0.25 g).…”
Section: Metabolite Profiling and Identificationmentioning
confidence: 99%